Bhinneka Tunggal Ika: the urgency of building character education in maintaining unity - Mufid, Ahmad; Sundawa, Dadang (Universitas Ahmad Dahlan, 2023)
Character education is pivotal in enhancing the quality of national education implementation. Amidst a backdrop of dwindling moral integrity, characterized by a pervasive character crisis, the very essence of the nation's ethos and cultural integrity is under perpetual threat, particularly in the era of globalization. Recognizing the unstoppable tide of globalization, nations are compelled to formulate strategic policies to mitigate the infiltration of values detrimental to national unity and cohesion while upholding the principle of Bhinneka Tunggal Ika, advocating for complete unity. Indonesia, with its diverse tapestry of ethnicities, religions, races, and tribes, embodies a divine essence deserving of reverence. Nevertheless, the imperative of a unifying symbol remains paramount to fortify against potential fragmentation. Proactive interventions in character education are indispensable to address conflicts that imperil national unity and integrity. As an inherently preventative measure, character education is instrumental in nurturing and enlightening future generations, countering societal schisms. This study adopts a literature review methodology to explore pertinent references and address contemporary challenges. Character education, contextualized within the framework of Bhinneka Tunggal Ika, resonates deeply with Indonesia's heterogeneous society, underscoring its significance in cultivating national character in harmony with the nation's motto. In conclusion, character education serves as a bulwark against the erosion of moral values amidst globalization, promoting unity and integrity within the diverse fabric of Indonesian society. This research contributes to the discourse on character education's role in fostering national cohesion, offering insights for policymakers and educators alike.